Monitoring of Hemostasis Parameters During Coronary Thrombolysis with Recombinant Tissue-Type Plasminogen Activator - Stump, D C; Topol, E J; Chen, A B; Hopkins, A; Collen, D (Thrombosis and Haemostasis, 1988)
The monitoring of changes in the blood coagulation and fibrinolytic systems during thrombolytic therapy with recombinant tissue-type plasminogen activator (rt-PA) may be complicated by artifacts due to in vitro activation after blood collection and to interference of other agents (e. g., heparin) in the assays. In 106 patients with early acute myocardial infarction, infused with 150 mg of rt-PA (G11044) intravenously over 5 to 8 hours, blood samples were collected into liquid citrate supplemented with the plasmin inhibitor aprotinin (200 KlU/ml plasma) or on a lyophilized mixture of acidified citrate and the synthetic t-PA inhibitor D-Phe-Pro-Arg-CH2Cl (PPACK). A good correlation between precipitable (sulphite) and functional (clotting rate) fibrinogen levels was observed in plasma collected on citrate before therapy (r = 0.76) and in samples collected after 3 hours on either aprotinin (r = 0.87) or PPACK (r = 0.82). Precipitable fibrinogen levels were approximately 10% higher than functional level, in baseline samples collected on citrate alone and approximately 20% higher in 3 hour samples collected on either PPACK or aprotinin. Fibrinogen levels measured with both assays correlated well, but were somewhat higher in samples collected on PPACK than on aprotinin. rt-PA antigen levels assayed in plasma collected in either inhibitor correlated well (r = 0.90) but were 10-20% higher in PPACK containing samples. Addition of heparin up to 9 units/ml to plasma had no effect on the functional fibrinogen assay.Even with these precautions for assay artifact, a very poor correlation (r =-0.15) was observed between the plasma rt-PA level and the residual functional fibrinogen level, both after 3 hours and towards the end of the rt-PA infusion. A decrease of the fibrinogen level at the end of the infusion to below 1 g/l was observed in 36% of the patients and to below 0.5 g/l in 11%. Optimal monitoring of hemostasis during rt-PA infusion is achieved by fibrinogen assays with a clotting rate method on samples collected on either PPACK or aprotinin. Heparin at therapeutic levels does not interfere with this assay.
Keywords: Thrombolytic therapy; Fibrinogen assays; In vitro fibri; nogenolysis; Fibrinolysis; Laboratory monitoring